THE AB INITIUAL AIR TRAFFIC CONTROLLERS CABABILITY FOR MAINTAINING RADIOTELEPHONY USING THE ENGLISH LANGUAGE - Питель, О. (Proceedings of National Aviation University, 2012)
The radiotelephony as the obligatory condition of ab initiual specialists training is outlined. As a result, its aim, object, subject, spheres of application and components have been determined. It is well- proven that for successful realization of professional activity it`s necessary to maintain effective communication in different aviation modes.The role of radiotelephony as a key component in ab initiual air traffic controllers work is determined